Application of ultraviolet radiation to control microbiologically influenced corrosion: a case study on soil sample from mangrove - Ali, M. K. F. B. M. (Taylors University, 2016)
Microbiologically influenced corrosion (MIC) is significant to the presence of microorganisms such as sulfate reducing bacteria (SRB) in the deterioration of metallic and non-metallic materials. Bacterial chemical biocides are commonly used to disinfect microorganism effectively. Yet, the practice has some negative impact on the environment since the chemical content may cause pollution. A laboratory experimental investigation was conducted to explore the performance of Ultraviolet (UV) radiation in exterminating SRB as an option to replace biocides usage. The morphologies of the isolated Sg. Ular SRB used in this study were related to Desulfovibrio species. An experimental work was conducted in determining the optimum pH and temperature for the SRB to grow before disinfection purposes. The experimental result showed optimum growth for respective SRB were at pH of 8.5 with temperature recorded at 37°C. UV radiation with wavelength of 254 nm was utilised to disinfect the microorganism. SRB samples were exposed to UV radiation for one hour and left incubated for 21 days. It was found that the percentage of metal loss in a sample exposed to UV radiation was lower compared with untreated sample. Results from the study revealed that UV has a potential as a viable option for SRB disinfection purposes and may be further developed to reduce the consumption of chemical biocides in pipeline maintenance scheme.